the Financial Literacy of Padang 3 Vocational High School Students in the Digital Era - Dessyta Gumanti; Reni Respita; Salman M. Noer; Caterina Lo; Detman Detman; Serli Diovani Teza; Widya Astuti (Jurnal Nusantara Berbakti, 2023)
: Financial literacy literacy in the digital era is very much needed, especially in the new normal era after the Covid-19 pandemic. Financial literacy is also very important to be implemented from an early age because it relates to the ability to manage and make the right financial decisions. The service activities carried out aim to provide reinforcement to students regarding financial literacy in the digital era for students of SMKN 3 Padang. Activities carried out by direct observation method. Before the community service activities were carried out, students were given a pretest to find out the extent of students' basic knowledge regarding financial literacy. The activity continued with the provision of material and discussion, finally a post-test was given to see students' understanding of material regarding financial literacy in the digital era. The survey conducted on participants found that this activity provided reinforcement of financial literacy that they had understood so far to be able to apply it from an early age in managing finances. The results of these activities provide strengthening of knowledge to students regarding financial literacy in the digital era and the formation of students' understanding of financial literacy so that it can be applied in students' daily lives, especially in the current digital era.